Sudden out‐of‐hospital cardiac arrest in pediatric patients in Kyushu area in Japan. Issue 12 (8th July 2021) - Yoshinaga, Masao; Ishikawa, Shiro; Otsubo, Yoshikazu; Shida, Masanori; Hoshiko, Kiyomi; Yatsunami, Koichi; Kanaya, Yoshiaki; Takagi, Junichi; Takamura, Kazushi; Ganaha, Hitoshi; Sunagawa, Makoto; Soeda, Osamu; et al.
Abstract: Background: It is well‐known that a neurologically favorable outcome of out‐of‐hospital cardiac arrest (OHCA) is associated with the presence of bystander‐initiated cardiopulmonary resuscitation (bystander CPR) and use of an automated external defibrillator. However, little is known about the effect of the presence of pre‐existing conditions, prior activity, and locations on the outcome of pediatric OHCA. Methods: We analyzed the data from questionnaires about pediatric patients with OHCA aged from 3 days to 19 years in the Kyushu area in Japan between 2012 and 2016. Results: A total of 594 OHCA cases were collected. The numbers of OHCA cases and the rate of 1 month survival with a favorable neurological outcome during sleeping, swimming / bathing, and exercise were 192 (1.0%), 83 (32.5%), and 44 (65.9%), respectively. When an OHCA occurred at school ( n = 56), 88% of children / adolescents received bystander CPR, but when it occurred at home ( n = 390), 15% received bystander CPR. Cardiovascular ( n = 61), suicide ( n = 61), and neurological / neuromuscular ( n = 44) diseases were three major pre‐existing conditions. The OHCA of cardiovascular disease was associated with exercise (24/61) and mainly occurred at school (22/61). The OHCA of neurological / neuromuscular disease was associated with swimming/bathing (15/44) and mainly occurred during bathing at home (12/44). Multivariate regression analysis showed that the presence of bystander CPR ( P < 0.001) and occurrence of OHCA at school ( P < 0.001) were independently predictive of a favorable outcome in pediatric OHCA. Conclusion: The outcome was different among pre‐existing conditions, prior activity, and location of OHCA. These findings might be useful for preventing OHCA and improving the outcome of pediatric OHCA.